PENGARUH SISTEM PENGENDALIAN INTERNAL, DAN GOOD CORPORATE GOVERNANCE TERHADAP KUALITAS LAPORAN KEUANGAN BPRS DI WILAYAH KERJA KANTOR OTORITAS JASA KEUANGAN MALANG - David Wahyu Hemawan; Nur Diana; M. Cholid Mawardi (Universitas Islam Malang, 2020)
The purpose of this study was to determine the influence of the Internal Control System and Good Corporate Governance on the Quality of BPRS Financial Statements in the Work Area of the Malang Financial Services Authority Office. The sample used was purposive sampling and obtained 37 respondents. This study applies multiple linear regression models. The results of the study of the Internal Control System have no significant effect on the Quality of Financial Statements. Good Corporate Governance has a positive effect on the Quality of Financial Statements. Keywords: Internal Control System, and Good Corporate Governance, and Quality of Financial Statements